Provisions of International Responsibility in Accordance with the Rules of International Law - Mishary Ali Alshaikhi (International Journal of Law Research and Studies, 2024)
The establishment of liability is considered a natural punishment in any legal system, whether through national legal systems, in particular the international community, and responsibility in this case arises, regardless of the person who violates the provisions of national or international law, as a result of the error or unlawful act committed by the offending person, and the cause of damage to another person, which leads to the establishment of responsibility in favour of the latter against the person who committed an unlawful act, or refrained from doing a legitimate act, and the cause of this act or omission is harmful to another person. Based on the foregoing, international responsibility in the face of States and other persons of public international law addressed under international legal rules as a normal procedure resulting from the establishment of international responsibility as a result of violating the sources establishing international legal rules, namely either international treaties, international custom or even general principles of law, where the State that violated the provisions and rules of international law is obliged to compensate the State affected by the wrong or wrongful act, or by restoring the situation to their correct as much as possible, and the establishment of international responsibility in this case is considered an actual translation of the provisions and rules of international law through its practical application on the ground Reality. As a result of international law’s keenness to protect the international community and its rights from illegal practices, international responsibility must be established towards any person of public international law who has infringed on the rights of other persons, which has added some effectiveness to the rules of international law, unlike in the past when resorting to the settlement of disputes by peaceful means was almost impossible.